Immune infiltrates are prognostic factors in localized gastrointestinal stromal tumors - Rusakiewicz, Sylvie; Semeraro, Michaela; Sarabi, Matthieu; Desbois, Mélanie; Locher, Clara; Mendez, Rosa; Vimond, Nadège; Concha, Angel; Garrido, Federico; Isambert, Nicolas; Chaigneau, Loic; Brun-Ly, Valérie Le; et al. (Cancer research, 2013)
Cancer immunosurveillance relies on effector/memory tumor-infiltrating CD8+ T cells with a T-helper cell 1 (TH1) profile. Evidence for a natural killer (NK) cell-based control of human malignancies is still largely missing. The KIT tyrosine kinase inhibitor imatinib mesylate markedly prolongs the survival of patients with gastrointestinal stromal tumors (GIST) by direct effects on tumor cells as well as by indirect immunostimulatory effects on T and NK cells. Here, we investigated the prognostic value of tumor-infiltrating lymphocytes (TIL) expressing CD3, Foxp3, or NKp46 (NCR1) in a cohort of patients with localized GIST. We found that CD3+ TIL were highly activated in GIST and were especially enriched in areas of the tumor that conserve class I MHC expression despite imatinib mesylate treatment. High densities of CD3+ TIL predicted progression-free survival (PFS) in multivariate analyses. Moreover, GIST were infiltrated by a homogeneous subset of cytokine-secreting CD56bright (NCAM1) NK cells that accumulated in tumor foci after imatinib mesylate treatment. The density of the NK infiltrate independently predicted PFS and added prognostic information to the Miettinen score, as well as to the KIT mutational status. NK and T lymphocytes preferentially distributed to distinct areas of tumor sections and probably contributed independently to GIST immunosurveillance. These findings encourage the prospective validation of immune biomarkers for optimal risk stratification of patients with GIST. Cancer Res; 73(12); 3499-510. ©2013 AACR.
Gesehen am 24.01.2022